Komunitas Basis Gerejawi dalam Perpektif Yohanes 6:1-15: Sebuah Analisis Naratif - Udu, Fransiskus Nala Kartijo (JURNAL LEDALERO, 2024)
This article is intended to reflect the life of the Basic Ecclesial Communities (BEC) in the perspective of John 6:1-15. It has frequently occurred that when discussing the BEC, people typically refer to the passages found in the Acts of the Apostles as well as in Paul’s letters. It is very uncommon for Gospel stories to be applied as a reference in looking at the life of the BEC. The passage concerning the bread multiplication in the Gospel of John is an immense inspiring and meaningful story to comprehend the life of the BEC. In this story, Jesus multiplies bread not simply to meet the basic needs of the multitude, but also existentially transforms them from an anonymous group into a community in Him. This is brightly expressed in Jesus’ actions: gathering a lot of people, feeding them, then turning those people into invitees who “sat together” with Him. This noticeable action indirectly shows that He himself constituted the BEC and gave it the spirit of life. Therefore, the BEC life must be centered on an intimate relationship with Christ in the Word and Eucharist. Communion with Jesus is a source of life, strength and power in carrying out our mission as His followers in the world. Key words Basic Ecclesial Communities (BEC), bread multiplication, Word and Eucharist, communion